Applying Information Hiding in VANETs to Covertly Report Misbehaving Vehicles - Jose Maria de Fuentes; Jorge Blasco; Ana Isabel González-Tablas; Lorena González-Manzano (International Journal of Distributed Sensor Networks)
Vehicular ad hoc networks (VANETs) are a new communication scenario in which vehicles take an active part. Real-time reporting of misbehaving vehicles by surrounding ones is enabled by in-vehicle sensors and VANETs. Thus, sensors allow detecting the misbehavior whereas VANETs allow sending the report to the authority. Nevertheless, these reports should pass unnoticed by the reported driver to avoid his/her potential reprisals. Information hiding techniques could be used to allow vehicles to transmit information covertly. In this work, two mechanisms for vehicle reporting are proposed based on two information hiding techniques— subliminal channels and steganography . The approach is to embed information into beacon messages either in the signature process (subliminal channel) or altering the least significant bits of selected sensorial fields (steganography). Results show that the proposal is computationally feasible for current vehicular devices and that it is possible to configure the system to operate in highways, secondary roads, and urban maps.